Upaya Meningkatkan Keterampilan Shooting Bola Basket dengan Metode Kombinasi Permainan Target pada Siswa Kelas XI SMA Negeri 14 Surabaya - Ahmad Dani; Kuntjoro, Bambang Ferianto Tyahyo; Ririn Dwitjahjono (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2024)
Physical Education, Sports and Health (PJOK) is an important subject in Senior High School (SMA) which aims to improve students' physical, spiritual and social health. But, in essence, there are students who are less interested in learning PJOK. This is caused by several factors, such as uniform and less interesting learning methods. This study aims to determine the effectiveness of using games in optimizing high school students' interest in learning PJOK. The research method used is a literature study by reviewing several literature sources such as journals, scientific articles, and books. The results showed that the use of traditional games in learning PJOK can optimize high school students' interest in learning.